Tailoring the Void Space Using Nanoreactors on Carbon Fibers to Confine SnS2 Nanosheets for Ultrastable Lithium/Sodium‐Ion Batteries. Issue 4 (10th February 2022) - Cui, Zhe; He, Shu‐Ang; Zhu, Jinqi; Gao, Mengluan; Wang, Hao; Zhang, Hao; Zou, Rujia
Abstract: Herein, a rational design of SnS2 nanosheets confined into bubble‐like carbon nanoreactors anchored on N, S doped carbon nanofibers (SnS2 @C/CNF) is proposed to prepare the self‐standing electrodes, which provides tunable void space on carbon fibers for the first time by introducing hollow carbon nanoreactors. The SnS2 @C/CNF provides the stable support with greatly enhanced ion and electron transport, alleviates aggregation and volume expansion of SnS2 nanosheets, and promotes the formation of abundant exposed edges and active sites. The volume balance between SnS2 nanosheets and hollow carbon nanoreactors is reached to accommodate the expansion of SnS2 during cycles by controlling the thickness of SnO2 shells, which achieves the best space utilization. The doping of N, S elements enhances the wettability of the carbon nanofiber matrix to electrolyte and Li ions and further improves the electrical conductivity of the whole electrode. Thus, the SnS2 @C/CNF benefits greatly in structural stability and pseudocapacitive capacity for improved lithium/sodium storage performance. As a result of these improvements, the self‐standing SnS2 @C/CNF film electrodes exhibit the highly stable capacity of 964.8 and 767.6 mAh g −1 at 0.2 A g −1, and excellent capacity retention of 87.4% and 82.4% after 1000 cycles at high current density for lithium‐ion batteries and sodium‐ion batteries, respectively. Abstract : The self‐standing electrodes consisting of SnS2 nanosheets confined inside the hollow carbon nanoreactors anchored on the N, S‐doped carbon fibers are prepared as lithium‐ion battery and sodium‐ion battery anodes. The precisely designed hollow nanoreactors on carbon fibers play a multifunctional role in improving the electrochemical performance of SnS2 nanosheets in lithium/sodium storage.